Antioxidant and Atibacterial Activities of Nipah (Nypa fruticans) against Vibrio sp. Isolated From Mud Crab (Scylla sp.) - Imra Imra; Kustiariyah Tarman; Desniar Desniar (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
AbstractNipah (Nypa fruticans) is the potential plant for source of active compound such as antioksidant and antibacterial substances. The plants are dispersed in Sumatera, Kalimantan, Sulawesi, Maluku and Papua Island. The aim of this research were determine the antioxidant and antibacterial activity from of nipah (fruit and leaf) that it extraction with methanol, and than determine toxicity and active compound contained in this extract. Diffusion agar and DPPH method were use for antibacterial and antioxsidant assay, respectively. Antioxsidant activity from nipah’s leaf extract was more effective (22,5 μg/mL) than nipah’s fruit extract (415 μg/mL). This activity to be classified to the strong antioxidant activity (IC50<50 μg/mL). The antibacterial activity from leaf extract was strong to inhibited Vibrio sp. with inhibition zone 8,75 mm. The crude extract of nipah’s leaf was toxic with toxicity value is 663,598 μg/mL. Flavonoids, steroids, tanin, saponin and phenol hidroquinon were the active compounds contained in the extract of nipah’s leaf.